Epidemiological analysis of hydrometra and its predictive value in gynecological tumors - Wu, Jianfa; Wang, Sihong; Zhang, Li; Wu, Suqin; Liu, Zhou (Frontiers in Oncology, 2023)
Introduction Hydrometra is a common gynecological disease, especially in postmenopausal women. However, its epidemiology, harmfulness, and value in predicting gynecological tumors have not been clearly elucidated. Methods In this study, the prevalence rate of and risk factors for hydrometra were investigated in 3,903 women who underwent screening for gynecological diseases at Zhoupu Hospital in Shanghai from 1 January to 31 December 2021. In addition, pathological distribution of hydrometra and its predictive value in gynecological tumors were studied in another 186 patients in whom hydrometra was diagnosed sonographically at Zhoupu Hospital, from 1 January 2020 to 31 December 2021, and who underwent hysteroscopy and postoperative pathological examination. Results The observed prevalence rate of hydrometra was 10.86%, which was higher than the prevalence of other gynecological diseases. Univariate and multivariate analysis indicated that advanced age (OR 1.11) and vaginitis (OR 3.18) were independent risk factors for hydrometra. Among 186 patients with a sonographic diagnosis of uterine fluid, simple hydrometra accounted for 34.41% of cases, inflammation accounted for 16.23%, and hematometra accounted for 2.15%, while gynecological tumors accounted for 5.91%. Moreover, univariate and multivariate analysis indicated that a higher body mass index (>23.92 kg/m2), greater hydrometra volume (i.e., distance between the two layers of endometrium>4.75 mm), and abnormal vaginal bleeding were high-risk predictive factors for gynecological tumors. Discussion In conclusion, hydrometra is a common disease, and is a risk factor for endometrial cancer and cervical cancer, especially in patients with higher hydrometra volume, higher BMI, and abnormal vaginal bleeding. It is necessary to pay more attention to hydrometra.